Task-Based Language Teaching for EFL Writing Development - Liando, Nihta V. F.; Rorimpandey, Rinny (English Education Department, 2025)
One aspect of English that is difficult for students to master is writing, because it requires the right method/technique in teaching after the pandemic. For this reason, this research was appointed, with the aim at knowing whether the TBLT method has an impact on the students' English learning process, especially for their writing skill. This research was conducted in class VIII of junior high school students, because this is an experimental study, a pre-experimental design is used with the type of one-group pre-test and post-test. In addition, in assessing the writing of students, this study adapts the writing rubric of (Brown, 2007). The results showed that TBLT has a very significant effect on students' writing, this can be seen in the mean scores of the pre-test and post-test. However, considering also the situation of students at the time of the study, it is hoped that further researchers or readers can examine more deeply about the learning losses found in this study or can use the results of the research as a starting point for learning problems during the new normal.